Cation-responsive turn-on fluorescence and absence of heavy atom effects of pyridyl-substituted triarylmethyl radicals. Issue 6 (4th January 2018) - Hattori, Yohei; Kimura, Shun; Kusamoto, Tetsuro; Maeda, Hiroaki; Nishihara, Hiroshi
Abstract : Pyridyl-substituted triarylmethyl radicals showed cation-responsive turn-on fluorescence and did not suffer from quenching by internal and external heavy atom effects. Abstract : Pyridyl-substituted triarylmethyl radicals exhibited cation-responsive turn-on fluorescence when additional pyridyl rings were incorporated at an appropriate position; the mechanism of fluorescence enhancement is examined. Reduced quenching by internal and external heavy atom effects is proposed as a unique property of fluorescent radicals, which can be utilized in different environments to conventional closed-shell fluorescent molecules.